Osteoarthritis Therapy: Which is More Effective, Laser Therapy or a Combination of TENS IR? - Aisyah; Vivera Pane, Rita; Yuriske Agnovianto; Tsabitah Husna (UNUSA Press, 2025)
Background: Osteoarthritis (OA) is a degenerative disease of the joints that attacks the joint cartilage and is one of the types of arthritis disease commonly found in older people. Knee osteoarthritis is one of the most common types of arthritis. Some treatments that can be performed are non-pharmacological therapies: Low Level Laser Therapy (LLLT), Transcutaneous Electrical Nerve Stimulation (TENS) and Infra Red (IR). Their function are to reduce the severity of pain and therefore reducing disability in knee joint pain patients. Objective of the study: to compare the effectiveness of non-pharmacological treatment of LLLT and combination of TENS IR in patients with knee osteoarthritis at RSI A Yani Hospital Surabaya. Method and Result: A quantitative approach was applied using a twogroup post-test-only experimental design to analyze the influence of independent treatments on pain reduction. The study was conducted from February to August 2024. Participants were selected through purposive sampling based on predefined criteria. Data normality was assessed using the Kolmogorov-Smirnov test. Since the data were not normally distributed, the Mann-Whitney U test was used to determine statistical differences between the two treatment groups. The statistical analysis using the MannWhitney test yielded a p-value of 0.417 (p > 0.05), indicating no significant difference in pain reduction between the LLLT group and the TENS+IR group. Conclusion: The findings suggest that both LLLT and the combined use of TENS and IR are equally effective in managing knee pain in osteoarthritis patients. As neither treatment showed superior outcomes, both can be considered valid non-pharmacological options in OA pain management protocols. Further studies with larger sample sizes and longitudinal assessment are recommended to confirm and expand upon these findings.